KORELASI FAKTOR RISIKO USIA PASIEN DENGAN KASUS DAN BIAYA RAWAT INAP PENYAKIT JANTUNG DI INDONESIA (ANALISIS SERIAL WAKTU PROGRAM JAMINAN KESEHATAN NASIONAL 2015-2021) - Hasibuan, Syarif Rahman; Prasetyo, Sabarinah; Darmawan, Ede Surya (Jurnal Ekonomi Kesehatan Indonesia, 2023)
This study analyzes the correlation between patient age with hospitalization cases and cost in Indonesia. The design of this study was cross-sectional quantitative using open sources data from Indonesia National Health Insurance Agency (BPJS Kesehatan). The sample units in this study were hospitalization cases from 2015-2021 of National Health Insurance program member. Sample size of this study are 43,921 that weighted to get 3,901,373 hospitalization cases. This study show an uptrend in cases and the total cost of cardiovascular disease hospitalization in 2015-2019, while it show downtrend during the Covid-19 pandemic. The average cost of cardiovascular disease hospitalization per case is 7.5 million rupiah (495.15 USD) per year. The highest average cost per case is 185.47 million rupiah (12,244.62 USD) per year; the lowest is 1.5million rupiah (99.03 USD) per year; and the average total cost is 3.99 trillion rupiah (263,417.41 USD) per year. The accumulated costs for 2015-2021 is 27.94 trillion rupiah (1,844,582.04 USD). Spearman's test shows there is a correlation between age and cases, average and total costs of cardiovascular disease hospitalization. Only correlation between age and average cost that show a negative pattern, which means that the higher the age, the lower the hospitalization average cost.